Development of Tropical Cyclone over the Bay of Bengal during South West Monsoon (The Dhaka University Journal of Earth and Environmental Sciences, 2021)
South West Monsoon (SW Monsoon) and Tropical Cyclone (TC) are two important weather systems for Bangladesh. During SW Monsoon i.e. during rainy season Bangladesh gets 70% to 85% of her annual rainfall. TC accompanied with strong gale winds, tornadoes, torrential rains and storm surges is considered as a deadly natural disaster. TC’s are mostly formed during pre-monsoon and post-monsoon season, but not uncommon during SW monsoon. This study consults the best track data (cyclone e-atlas) of India Meteorological Department (IMD) containing tracks of cyclones and depression over North Indian Ocean (NIO) for the years 1891 to 2020 i.e. of 130 years. In these 130 years, among total 1219 storms, 608 had formed during SW monsoon. If only Cyclonic Storms (CS) and Severe Cyclonic Storms (SCS) are considered then, 150 storms formed during SW Monsoon. This paper studied two cyclogenesis factors; vertical wind shear and upper level anticyclone for eight cases of tropical storms formed during SW Monsoon. Besides cyclogenesis factors, influence of Madden Julian Oscillation (MJO) is also studied. Threat analysis associated with tropical storms during SW Monsoon has been done which might help in planning of National Disaster Management Program.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 10(1), 2021, P 57-65